Pendampingan Pembuatan Profil Kawasan Ekowisata Mangrove Telok Berdiri, Desa Sungai Kupah, Kecamatan Sungai Kakap, Kabupaten Kubu Raya - Andri Andri; Rakhmad Perkasa Harahap; Siti Aprizkiyandari; Leony Agustine M (Cv. Utility Project Solution, 2022)
Sungai Kupah Village has a tourism awareness group (POKDARWIS) consisting of 30 people. Most of the group members work as fishermen or coconut gardeners. The tourist sites managed by the group are in the form of mangrove tourism. The tour is equipped with mangrove tracking facilities, photo spots, canteens, toilets, parking lots. During the pandemic, the number of tourists fell by almost 70%. Another factor that causes the low number of visitors is the lack of information about the location profile of digital-based mangrove ecotourism areas. Promotion is an important activity that plays an active role in introducing information and information about potential products so that a wider audience can understand their existence and can encourage audiences to visit the product or object to be opened. It is hoped that knowledge about the role and importance of mangroves can be disseminated to the wider community through this tourist attraction. One of the promotional steps that can be taken is to create a digital-based profile of the location of the mangrove ecotourism area, where all information will be conveyed to the public to build brand awareness. Lecturers play a role in implementing the Tri Dharma of Higher Education, namely Community Service in the form of participating in empowering and interacting with the community. in Community Service partners, namely POKDARWIS Ekowisata Standing, which is to improve the skills of mangrove tourism management partners in marketing tourism objects, producing mangrove tourism profile videos uploaded on social media and can increase visitors who come to mangrove tourism